Ceria-based catalysts for low-temperature selective catalytic reduction of NO with NH3. Issue 5 (18th December 2015) - Tang, Changjin; Zhang, Hongliang; Dong, Lin
Abstract : Low-temperature NH3 -SCR has attracted considerable attention owing to the vast demand in industrial furnaces and its energy-conserving feature. This review summarizes the recent advances in the application of ceria-based catalysts for low-temperature NH3 -SCR. Abstract : Selective catalytic reduction of NO with NH3 (NH3 -SCR) is a powerful technique for the abatement of NO x from stationary sources, and the currently used VO x /TiO2 -based catalysts are widely applicable for medium-temperature conditions but not suitable for NH3 -SCR operated at low temperatures. Recently, low-temperature NH3 -SCR has attracted considerable attention owing to the vast demand in industrial furnaces and its energy-conserving feature. During the past years, a great many studies have demonstrated that ceria-based catalysts are potential candidates as catalysts for low-temperature NH3 -SCR. Herein we summarize the recent advances in the application of ceria-based catalysts for low-temperature NH3 -SCR. The review begins with a brief introduction of the general guideline for low-temperature NH3 -SCR and the interaction between the reactants and CeO2 . The different roles of ceria as a pure support/active species, bulk doping component and surface modifier are discussed. As well, the mechanistic investigations (active sites, intermediates, reaction mechanism) and SO2 /H2 O tolerance are emphasized. Lastly, the perspectives on the opportunities and challenges of ceria-based catalysts for low-temperature NH3 -SCR in future research are presented.